Making Kokedama as an Implementation of Ecological Awareness at NSA Surabaya High School - Afnan, Muhammad Zahrudin; Utomo, Budi; Purana, I Putu Tony (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2025)
The global environmental crisis is not just a warning, but a call to action, and education is key. NSA Surabaya High School addresses this challenge through the unique learning innovation of kokedama, a Japanese art of farming that combines aesthetics and sustainability. More than just the practice of planting, kokedama is a powerful medium to instill ecological awareness in the younger generation. With a hands-on method combined with affective reflection, students not only learn farming skills, but also develop a deep empathy for nature and a real sense of ecological responsibility. This finding proves that contextual education can be a concrete solution to instill environmental awareness, solution to instill environmental awareness from an early age. We recommend this activity as a revolutionary strategy to create a generation of high school students who not only care but are also ready to lead the change for the sustainability of our planet.